Dancing around the divisome: asymmetric chromosome segregation in Escherichia coli. - Wang, X; Possoz, C; Sherratt, D (2005)
By simultaneously tracking pairs of specific genetic regions and divisome proteins in live Escherichia coli, we develop a new scheme for the relationship between DNA replication-segregation, chromosome organization, and cell division. A remarkable asymmetric pattern of segregation of different loci in the replication termination region (ter) suggests that individual replichores segregate to distinct nucleoid positions, consistent with an asymmetric segregation of leading and lagging strand templates after replication. Cells growing with a generation time of 100 min are born with a nonreplicating chromosome and have their origin region close to mid-cell and their ter polar. After replication initiation, the two newly replicated origin regions move away from mid-cell to opposite cell halves. By mid-S phase, FtsZ forms a ring at mid-cell at the time of initiation of nucleoid separation; ter remains polar. In the latter half of S phase, ter moves quickly toward mid-cell. FtsK, which coordinates the late stages of chromosome segregation with cell division, forms a ring coincident with the FtsZ ring as S phase completes, approximately 50 min after its initiation. As ter duplicates at mid-cell, sister nucleoid separation appears complete. After initiation of invagination, the FtsZ ring disassembles, leaving FtsK to complete chromosome segregation and cytokinesis.